Correlation of MRI features of urethral diverticulum and pre‐ and post‐operative stress urinary incontinence. Issue 1 (9th November 2018) - Seth, Jai H.; Naaseri, Sahar; Solomon, Eskinder; Pakzad, Mahreen; Hamid, Rizwan; Ockrim, Jeremy; Greenwell, Tamsin J.
Abstract : Aims: The complexity of urethral diverticulectomy depends on location, size, and degree of circumferential involvement. MRI features were examined to predict functional outcome after surgery for urethral diverticulum (UD). Methods: A prospectively acquired database was of all patients who have had surgical excision of UD at a tertiary center since 2004 was reviewed. Particular focus was pre‐ and post‐operative urodynamically proven stress urinary incontinence (USUI), and pre‐operative MRI features. MRI parameters included diverticular volume, degree of circumferential involvement around the urethra, distance of the Os of UD to bladder neck and urethral length. Students t ‐test and Mann‐Whitney U ‐test were used to compare rates of de novo USUI. Results: There were 100 patients (mean age 45.8 yrs), who had excision of UD since 2004, with a minimum follow‐up of 10 months (range 10‐112 months). Full MRI data was available for 83 patients. Fourteen were of simple configuration (16.8%), 32 were horseshoe (38.6%), and 37 (44.6%) were circumferential. Twenty‐five (25%) patients had pre‐operative USUI, while 12 (12%) patients developed de novo USUI post‐excision. While, the majority of patients with de novo USUI (67%) had >270° circumferential involvement of urethra, the pre‐operative diverticular volume did not predict the likelihood of USUI developing ( P  = 0.3). A shorter urethral length was associated with pre‐operative USUI. Conclusions: 25% of all patients had pre‐op USUI, and diverticular volume and urethral length was significantly smaller in this group. The majority of patients with de novo USUI had complex diverticula configuration with higher baseline circumferential angle around urethra, with 67% of angle's between 270 and 360°